Using Vapor Generation Equipment to Create Artificial Rain: The Design and Function of a New System - Hideyo Murakami (Journal of Basic & Applied Sciences, 2021)
The incidence of water shortage events – including drought, forest fire, and desertification – is rapidly increasing due to global warming. This paper shows the principles and the practical application of a new artificial rain system that would help prevent these types of harmful water shortage events. The proposed artificial rain system is composed of solar-powered vapor generation equipment that floats on a large body of water. From this water, vapor is generated by means of solar energy. This vapor is transformed into clouds. These clouds are transported to an area experiencing water shortage, and these clouds provide rain to the target area. The proposed artificial rain system can be designed to provide a specific amount of rain, to be applied at a pre-determined time, to a specified area. This equipment is operated by solar power, so does not produce any CO2emissions. The detailed design example shown in this paper demonstrates that a vapor generation equipment group 1,080km square in area can make 1,200 kg of vapor per square meter per one year, and provide precipitation for an agricultural area 9,720 km square. The advantages and disadvantages of this system are considered. The estimated cost to produce one kilogramme of precipitation water by the proposed artificial rain system is about 0.002USD.